Organizacja procesu budowy systemów wczesnego ostrzegania - Szpulak, Aleksandra (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This article presents the main steps of building an early warning system process. These steps are based on the literature studies and empirical research on Polish companies corporate liquidity. The author also defines some crucial ideas connected with building early warning system such as an early warning system, warning horizon or possible warning signals. She points out its interpretation and application in management. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (19); 2007; nr 1180, s. 85-96